Adsorptive Properties of Template-Containing Silica-Based MCM-41 and MCM-50 Materials - F.M. Bobonich; A.S. Kovalenko; Yu.G. Voloshina; A.S. Korchev; V.N. Solomakha; A.P. Philippov; V.G. Il'in (Adsorption Science & Technology)
Template-containing silica-based MCM-41 and MCM-50 materials have been shown to have microporous adsorbent properties, with the characteristic adsorption energy in such micropores being strongly dependent on the molecular mass of the adsorptives employed. The total adsorption volume was found to decrease as the molar volume of the adsorptive increased. A model explaining the peculiarities of the adsorptive properties of the template-containing materials is proposed.